Cross-Cultural Experiences of Belt and Road Students in Chinese Prefectural Medical Centers: A Mixed-Methods Study - Li, Xixi; Yang, Bo; Jin, Daoxin; Zhou, Tong; Zhao, Zhonglei; Li, Xiaomei; Wang, Xiquan (Celebes Nursing Journal, 2025)
Introduction The Belt and Road Initiative has increased international student enrollment in China, bringing challenges like diverse student preparedness and cross-cultural adaptation issues. Effective adaptation is essential for students' academic success and mental health, yet limited research exists on medical students' adaptation in China’s prefectural cities. Objectives This study is to examine the levels of cultural adaptation stress, psychological resilience, loneliness, and coping strategies among international medical students studying in clinical medical centers in China, explore the relationships between these factors, and identify the main challenges they face along with their support needs, providing recommendations for future interventions and policies. Design A convergent mixed methods approach was used, with quantitative data collected via “Questionnaire Star” using scales for Cultural Adaptation Stress, Psychological Resilience, Loneliness, and Coping Style. Qualitative data were gathered through semi-structured focus groups, analyzed thematically. Methods The study was conducted in a medical center in a prefectural city in Sichuan, China, recruiting 25 international students for surveys and 20 for focus groups. Results Mean scores for Acculturative Stress, Resilience, Loneliness, and Coping were 127.4 ± 17.8, 70.0 ± 12.2, 46.2 ± 6.1, and 144.7 ± 15.9, respectively. Coping correlated positively with resilience (r = 0.464, P < 0.05) and negatively with loneliness (r = -0.450, P < 0.05). Four themes emerged: motivations for studying in China, cross-cultural experiences, challenges, and training needs. Conclusion Students from Belt and Road Initiative countries face adaptation challenges in China. Enhancing coping strategies and providing targeted support may improve their cross-cultural adaptation and well-being.